2014
DOI: 10.5935/abc.20140179
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Neutrophil-To-Lymphocyte Ratio and Electrocardiographic Ischemia Grade in STEMI

Abstract: BackgroundNeutrophil-to-lymphocyte ratio (NLR) has been found to be a good predictor of future adverse cardiovascular outcomes in patients with ST-segment elevation myocardial infarction (STEMI). Changes in the QRS terminal portion have also been associated with adverse outcomes following STEMI.ObjectiveTo investigate the relationship between ECG ischemia grade and NLR in patients presenting with STEMI, in order to determine additional conventional risk factors for early risk stratification.MethodsPatients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Our study revealed that among 211 patients, 181 of them (85.8%) were male and 30 of them (14.2%) were female which is accordance with the results of other studies which report that acute myocardial infarction happens more in men compared to women (16)(17)(18)(19)(20)(21)(22).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Our study revealed that among 211 patients, 181 of them (85.8%) were male and 30 of them (14.2%) were female which is accordance with the results of other studies which report that acute myocardial infarction happens more in men compared to women (16)(17)(18)(19)(20)(21)(22).…”
Section: Resultssupporting
confidence: 91%
“…In a study carried out in turkey it was shown that NLR was significantly higher in patients with grade 3 ischemia. The researchers in this article believe that it is possible to use NLR as a prognostic and risk assessment index in patients with acute myocardial infarction in near future (20), which is in correspondence with the results of our manuscript.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies demonstrated that NLR is a significant predictor of adverse outcomes for patients with conditions such as acute cholecystitis, cardiovascular disease, cerebrovascular disease, malignancies, and sudden sensorineural hearing loss . In rheumatoid arthritis, NLR correlates with the disease activity score and high values are associated with chronic conditions such as diabetes, as well as with smoking and increased age .…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil‐to‐lymphocyte ratio (NLR), calculated as ANC divided by absolute lymphocyte count (ALC), is a powerful parameter for predicting the prognosis or severity of disease . NLR is believed to reflect the balance between the innate (neutrophils) and adaptive (lymphocytes) immune responses, and elevated values are associated with cellular DNA damage .…”
Section: Introductionmentioning
confidence: 99%